FIROKIY AND PARTAV (Scientific journal of the Fergana State University, 2024)
In this article, some of poems Dusmuhammad Firoqiy are analysed which related to Sufism. There have been given discusses about Firokiy’s writing skills in this way by his one of the ghazals. In addition, a conclusion was made about the author's skill in this regard, using the examples of words and phrases, and symbols that were used in it.